Polymer containing sulfur-oxygen bonds as well as preparation method and application thereof

By using sulfur-containing oxygen bonds as electrode materials, the problem of insufficient adsorption capacity of traditional electrode materials on sodium ions is solved, efficient sodium ion adsorption and desalination effects are achieved, and the application performance of capacitance deionization technology is improved.

CN119119397APending Publication Date: 2024-12-13JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411464986.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional electrode materials have limited adsorption capacity to sodium ions in capacitance deionization technology, which is difficult to meet practical application needs.

Method used

A polymer containing sulfur-oxygen bond is used as the electrode material to form amide bonds by reacting with tetraketone compounds to increase the active site of sodium ions and improve the adsorption capacity of sodium ions. The polymer preparation method includes mixing reactions under the protection of an inert gas, followed by cooling, centrifugation, washing, and finally mixing with conductive additives and binders to grind evenly onto conductive carbon cloth or carbon paper.

Benefits of technology

It provides excellent desalination capability, significantly improves the application prospects of capacitor deionization and sodium removal performance, and achieves efficient adsorption of sodium ions from seawater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119397A_ABST
    Figure CN119119397A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-oxygen bond-containing polymer as well as a preparation method and application thereof, and belongs to the technical field of capacitive deionization. The preparation method comprises the following steps: under the protection of inert gas, mixing a sulfur-oxygen bond-containing compound, a tetraketone compound, an initiator and an organic solvent, reacting in reflux, heating and stirring states, cooling to room temperature after the reaction is completed, centrifuging and washing to obtain a solid product, namely the sulfur-oxygen bond-containing polymer. According to the sulfur-oxygen bond-containing polymer as well as the preparation method and the application thereof, the polymer synthesized by reacting the sulfur-oxygen bond-containing compound and the tetraketone compound has a plurality of sodium ion active sites, so that the embedding of sodium ions is facilitated, and the purpose of adsorbing the sodium ions from seawater is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of capacitive deionization, and in particular to a polymer containing sulfur-oxygen bonds and a preparation method and application thereof. Background Art

[0002] About three quarters of the Earth is covered by water, but the vast majority of the water on Earth is seawater (96.5%) and brackish water (1%) that are difficult for humans to use directly, while most of the remaining 2.5% of fresh water is frozen in the polar regions and glaciers.

[0003] Traditional sodium ion removal and recovery technologies mainly include multi-stage flash evaporation, electrodialysis and multi-effect distillation, but they are often limited by complex structures, severe scaling and high maintenance costs. As a new technology, capacitive deionization technology has multiple advantages such as high energy efficiency, no secondary pollution, low operating costs and easy regeneration, which has attracted widespread attention. However, there are still few studies on the application of capacitive deionization technology for sodium removal.

[0004] Capacitive deionization technology (CDI) uses an external potential difference to make charged dissolved ions accumulate on the electrode surface to complete the ion adsorption. Due to the limited specific surface area available for ion adsorption, the desalination capacity of traditional carbon electrodes such as activated carbon and graphene is low and far from meeting the needs of practical applications. Therefore, in order to pursue higher deionization performance, the design of efficient electrode materials plays a vital role in the development and expansion of CDI practical applications and has become one of the current research hotspots. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a polymer containing sulfur-oxygen bonds and a preparation method and application thereof, which solves the problem that the existing electrode materials have limited ability to adsorb sodium ions.

[0006] To achieve the above object, the present invention provides a polymer containing sulfur-oxygen bonds, the structure of which is shown below:

[0007] Formula I

[0008] Formula II

[0009] Formula III

[0010] A method for preparing a polymer containing sulfur-oxygen bonds comprises: under the protection of an inert gas, mixing a compound containing sulfur-oxygen bonds, a tetraketone compound, an initiator and an organic solvent, reacting under reflux, heating and stirring, cooling to room temperature after the reaction is completed, centrifuging and washing to obtain a solid product, namely, the polymer containing sulfur-oxygen bonds.

[0011] Preferably, the molar ratio of the compound containing a sulfur-oxygen bond, the tetraketone compound and the initiator is 2:2:(3-4.3).

[0012] Preferably, the initiator is 4,4'-sulfonylbis(benzene-1,2-disodium);

[0013] The structural formula of the compound containing sulfur-oxygen bond is:

[0014] Preferably, when the tetraketone compound is pyrene-4,5,9,10-tetraketone, the compound containing sulfur-oxygen bonds undergoes polymerization reaction with pyrene-4,5,9,10-tetraketone, and the obtained polymer containing sulfur-oxygen bonds is of Formula I:

[0015]

[0016] When the tetraketone compound is 2,7-tert-butyl-4,5,9,10-tetraketone, the compound containing sulfur-oxygen bond undergoes polymerization reaction with 2,7-tert-butyl-4,5,9,10-tetraketone, and the obtained polymer containing sulfur-oxygen bond is of formula II:

[0017]

[0018] When the tetraketone compound is 1,3,6,8-tetrabromopyrene-4,5,9,10-tetraketone, the compound containing sulfur-oxygen bonds undergoes polymerization reaction with 1,3,6,8-tetrabromopyrene-4,5,9,10-tetraketone, and the obtained polymer containing sulfur-oxygen bonds is of formula III:

[0019]

[0020] Preferably, the heating is to react at 120° C. for 8-70 hours; and the washing is to wash with acetone and anhydrous ethanol in sequence.

[0021] An electrode material is prepared from the above-mentioned polymer containing sulfur-oxygen bonds. The preparation method includes: mixing and grinding the polymer containing sulfur-oxygen bonds, a conductive additive and a binder to obtain a slurry; uniformly coating the slurry on the surface of a conductive carbon cloth or conductive carbon paper, and obtaining the electrode material after drying.

[0022] Preferably, the mass ratio of the polymer containing sulfur-oxygen bonds, the conductive additive and the binder is 7:2:1; the conductive additive is acetylene black, and the binder is polyvinylidene fluoride.

[0023] The present invention discloses a polymer containing sulfur-oxygen bonds and a preparation method and application thereof, which have the following beneficial effects:

[0024] (1) The compound containing sulfur-oxygen bond reacts with tetraketone compound, and the carboxyl group of dianhydride and the amino group of diammonium undergo condensation reaction to form amide bond, while releasing water. This process gradually polymerizes and finally forms polyimide. The synthesized polymer has multiple sodium ion active sites, which facilitates the embedding of sodium ions, thereby achieving the purpose of adsorbing sodium ions from seawater.

[0025] (2) The provided polymer containing sulfur-oxygen bonds has excellent desalination ability as an electrode material for capacitive deionization, shows good application prospects in the field of capacitive deionization electrode materials, and provides a new idea for applying capacitive deionization technology to remove sodium.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the carbon NMR spectrum of the polymer (I) containing sulfur-oxygen bonds;

[0028] Figure 2 This is the carbon NMR spectrum of the polymer (II) containing sulfur-oxygen bonds;

[0029] Figure 3 This is the carbon NMR spectrum of the polymer (III) containing sulfur-oxygen bonds;

[0030] Figure 4 The cyclic voltammetry (CV) curves of the electrode sheet of the sulfur-oxygen bond-containing polymer (I) prepared in Example 1 of the present invention at different scanning rates;

[0031] Figure 5 The electrode sheet of the polymer containing sulfur-oxygen bond prepared in Examples 1 to 9 of the present invention is 1Ag -1 Comparison of mass specific capacity under current density;

[0032] Figure 6 The graph is a graph showing the change in conductivity of the conductive carbon cloth of the sulfur-oxygen bond-containing polymer (I) prepared in Example 1 of the present invention during the adsorption and desorption process in 500 mg / L NaCl electrolyte under different voltage conditions. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0034] Embodiment 1

[0035] A method for preparing a polymer containing sulfur-oxygen bonds, comprising:

[0036] 556.66 mg (2 mmol) of the polymer containing sulfur-oxygen bonds, 624.36 mg (2 mmol) of pyrene-4,5,9,10-tetraketone and 834.99 mg (3 mmol) of 4,4'-sulfonylbis(benzene-1,2-disodium) were added to the reactor under nitrogen protection and dissolved in 75 mL of acetic acid. The mixture was stirred continuously under reflux and reacted in an oil bath at 120°C for 12 hours. After the reaction was completed, the heating was stopped, the mixture was cooled to room temperature, the solid product was washed by centrifugation, washed with acetone 3 times, washed with ethanol 3 times, and dried under vacuum at 60°C to obtain the polymer containing sulfur-oxygen bonds (I), the structure of which is shown below:

[0037]

[0038] The reaction formula is as follows:

[0039]

[0040] like Figure 1 The figure shows the carbon NMR spectrum of the polymer (I) containing sulfur-oxygen bonds, which proves the successful synthesis of the compound.

[0041] Embodiment 2

[0042] The preparation method of the sulfur-oxygen bond-containing polymer (I) is the same as that of Example 1, except that the molar ratio of pyrene-4,5,9,10-tetraketone to the initiator is 2:3.3, that is, the amount of pyrene-4,5,9,10-tetraketone remains unchanged at 624.36 mg (2 mmol), while the amount of the initiator is changed.

[0043] Embodiment 3

[0044] The preparation method of the sulfur-oxygen bond-containing polymer (I) is the same as that of Example 1, except that the molar ratio of pyrene-4,5,9,10-tetraketone to the initiator is 2:4.3, that is, the amount of pyrene-4,5,9,10-tetraketone remains unchanged at 624.36 mg (2 mmol), while the amount of the initiator is changed.

[0045] Embodiment 4

[0046] The preparation method of the sulfur-oxygen bond-containing polymer (I) is the same as that of Example 1, except that the reaction is carried out in an oil bath at 120° C. for 48 hours.

[0047] Embodiment 5

[0048] The preparation method of the sulfur-oxygen bond-containing polymer (I) is the same as that of Example 1, except that the reaction is carried out under 120° C. oil bath conditions for 70 h.

[0049] Embodiment 6

[0050] The preparation method of the sulfur-oxygen bond-containing polymer (I) is the same as that of Example 1, except that the reaction is carried out in an ice-water bath for 12 hours.

[0051] Embodiment 7

[0052] The preparation method of the sulfur-oxygen bond-containing polymer (I) is the same as that of Example 1, except that 4,4'-sulfonylbis(benzene-1,2-disodium) is replaced by 1097.231 mg (4.3 mmol) of Cu(B F4)2.

[0053] Embodiment 8

[0054] A method for preparing a polymer containing sulfur-oxygen bonds, comprising:

[0055] 556.66 mg (2 mmol) of the polymer containing sulfur-oxygen bonds, 748.86 mg (3 mmol) of 2,7-tert-butyl-4,5,9,10-tetraketone and 834.99 mg (3 mmol) of 4,4'-sulfonylbis(benzene-1,2-disodium) were added to the reactor under nitrogen protection and dissolved in 75 mL of acetic acid. The mixture was stirred continuously under reflux and reacted in an oil bath at 120°C for 12 hours. After the reaction was completed, the heating was stopped, the product was cooled to room temperature, the solid product was washed by centrifugation, washed 3 times with acetone, washed 3 times with ethanol, and dried under vacuum at 60°C to obtain the polymer containing sulfur-oxygen bonds (II), the structure of which is shown below:

[0056]

[0057] The chemical reaction formula is as follows:

[0058]

[0059] The carbon NMR spectrum of the polymer containing sulfur-oxygen bonds (II) is as follows Figure 2 As shown, the successful synthesis of the polymer (II) containing sulfur-oxygen bonds was demonstrated.

[0060] Embodiment 9

[0061] 556.66 mg (2 mmol) of the polymer containing sulfur-oxygen bonds, 1155.6 mg (2 mmol) of 1,3,6,8-tetrabromopyrene-4,5,9,10-tetraketone and 834.99 mg (3 mmol) of 4,4'-sulfonylbis(benzene-1,2-disodium) were added to the reactor under nitrogen protection and dissolved in 75 mL of acetic acid. The mixture was stirred continuously under reflux and reacted in an oil bath at 120°C for 12 hours. After the reaction was completed, the heating was stopped, the mixture was cooled to room temperature, the solid product was washed by centrifugation, washed with acetone 3 times, washed with ethanol 3 times, and dried under vacuum at 60°C to obtain the polymer containing sulfur-oxygen bonds (III), the structure of which is shown below:

[0062]

[0063] The chemical reaction formula is as follows:

[0064]

[0065] like Figure 3 The figure shows the carbon NMR spectrum of the polymer (III) containing sulfur-oxygen bonds, which proves the successful synthesis of the polymer (III) containing sulfur-oxygen bonds.

[0066] Application Example 1

[0067] The electrode sheet of the polymer containing sulfur-oxygen bonds prepared in Examples 1 to 9 is prepared by:

[0068] The dried sulfur-oxygen bond-containing polymer was ground in a mortar to ensure a uniform mixture.

[0069] The ground sulfur-oxygen bond-containing polymer, acetylene and polyvinylidene fluoride are dispersed in 1-methyl-2-pyrrolidone (NMP) at a mass ratio of 7:2:1, and ground to form a uniform slurry.

[0070] The slurry was evenly suspended on conductive carbon paper and vacuum dried at 60° C. for 12 h to obtain a polymer electrode sheet containing sulfur-oxygen bonds for a working electrode.

[0071] Application Example 2

[0072] The conductive carbon cloth of the polymer containing sulfur-oxygen bonds prepared in Examples 1 to 9 is prepared by:

[0073] The dried sulfur-oxygen bond-containing polymer was ground in a mortar to ensure a uniform mixture.

[0074] The ground sulfur-oxygen bond-containing polymer, acetylene and polyvinylidene fluoride are dispersed in 1-methyl-2-pyrrolidone (NMP) at a mass ratio of 7:2:1, and ground to form a uniform slurry.

[0075] The slurry was evenly hung on the conductive carbon cloth, and vacuum dried at 60° C. for 12 h to obtain a polymer conductive carbon cloth containing sulfur-oxygen bonds for the working electrode.

[0076] Test Example 1

[0077] Electrochemical performance tests were performed on the electrode sheets of the polymer containing sulfur-oxygen bonds prepared in Examples 1 to 9.

[0078] The three-electrode system was used to electrochemically test the polymer electrode sheet containing sulfur and oxygen bonds in 0.5mM NaCl electrolyte. The results are as follows: Figure 1-2 shown.

[0079] Figure 4 The cyclic voltammetry (CV) curves of the electrode sheet of the sulfur-oxygen bond-containing polymer (I) prepared in Example 1 at different scanning rates are shown in FIG. Figure 4 Two pairs of obvious redox peaks can be observed, indicating that its redox property is good.

[0080] Figure 5 The electrode sheet of the polymer containing sulfur and oxygen bonds prepared in Examples 1 to 9 is 1Ag -1 Comparison of mass specific capacity under current density.

[0081] from Figure 5 It can be seen that when the reaction time increases, the mass specific capacity does not increase significantly; the mass specific capacity under oil bath conditions is significantly higher than that of the polymer containing sulfur and oxygen bonds obtained under ice water bath conditions; the mass specific capacity of the polymer using Cu(BF4)2 as an initiator is lower than that of the polymer containing sulfur and oxygen bonds using 4,4'-sulfonylbis(benzene-1,2-disodium) as an initiator. It can also be seen that when the tetraketone compound selected is pyrene-4,5,9,10-tetraketone, the mass specific capacity of the prepared electrode is the highest and the electrochemical performance is the best.

[0082] Test Example 2

[0083] Capacitive deionization performance test of the polymer conductive carbon cloth containing sulfur-oxygen bonds prepared in Examples 1 to 9

[0084] The polymer conductive carbon cloth containing sulfur-oxygen bonds was tested for desalination in a 50 mg / L electrolyte using a capacitive deionization system using an electrochemical workstation.

[0085] Figure 6 The conductivity of the conductive carbon cloth containing the sulfur-oxygen bond polymer (I) prepared in Example 1 during the adsorption and desorption process in a 50 mg / L electrolyte under different voltage conditions is shown in FIG. Figure 6 It can be seen that the polymer (I) containing sulfur-oxygen bonds prepared in Example 1 can achieve faster capacitive deionization.

[0086] The initial (30 min) adsorption capacity of the conductive carbon cloth containing sulfur-oxygen bond polymers prepared in Examples 1 to 9 in 50 mg / L electrolyte is shown in Table 1:

[0087] Table 1 Initial adsorption capacity of conductive carbon cloth with different sulfur-oxygen bond-containing polymers in 50 mg / L electrolyte

[0088] Test No. <![CDATA[Initial adsorption capacity / mg·g -1 > Embodiment 1 142.49 Embodiment 2 100.58 Embodiment 3 86.23 Embodiment 4 76.23 Embodiment 5 60.85 Embodiment 6 10.62 Embodiment 7 25.78 Embodiment 8 44.91 Embodiment 9 31.36

[0089] As can be seen from Table 1, the initial adsorption capacity of the conductive carbon cloth of the sulfur-oxygen bond-containing polymer (I) prepared in Example 1 is higher than that of other examples; Examples 2 and 3 illustrate that the performance is better when the molar ratio of pyrene-4,5,9,10-tetraketone to the initiator is 2:3, and Examples 4 and 5 illustrate that with the extension of the reaction time, the initial adsorption capacity of sodium ions is not significantly improved; Example 6 does not react under an oil bath, so that the initial adsorption capacity of sodium ions decreases significantly; Example 7 replaces the initiator, so that the initial adsorption capacity of sodium ions decreases to less than half of that of Example 1, indicating that not all initiators can achieve the same effect.

[0090] Because of the replacement of Example 8 and Example 9, the initial adsorption capacity of the obtained sulfur-oxygen bond-containing polymer for sodium ions also changed significantly, but it was still at a high stage. In comparison, the sulfur-oxygen bond-containing polymer (I) had the best adsorption performance for sodium ions.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A polymer containing sulfur-oxygen bonds, characterized in that Its structure is as follows: Formula I Formula II Formula III Among them, n=1-200.

2. A method for preparing a polymer containing sulfur-oxygen bonds, characterized in that: include: Under the protection of inert gas, a compound containing a sulfur-oxygen bond, a tetraketone compound, an initiator and an organic solvent are mixed and reacted under reflux, heating and stirring. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed to obtain a solid product, that is, a polymer containing a sulfur-oxygen bond.

3. The method for preparing a polymer containing sulfur-oxygen bonds according to claim 2, characterized in that: The molar ratio of the compound containing sulfur-oxygen bond, the tetraketone compound and the initiator is 2:2:(3-4.3).

4. The method for preparing a polymer containing sulfur-oxygen bonds according to claim 2, characterized in that: The initiator is 4,4'-sulfonylbis(benzene-1,2-disodium); The structural formula of the compound containing sulfur-oxygen bond is:

5. The method for preparing a polymer containing sulfur-oxygen bonds according to claim 4, characterized in that: When the tetraketone compound is pyrene-4,5,9,10-tetraketone, the compound containing sulfur-oxygen bonds undergoes polymerization reaction with pyrene-4,5,9,10-tetraketone, and the obtained polymer containing sulfur-oxygen bonds is of Formula I: When the tetraketone compound is 2,7-tert-butyl-4,5,9,10-tetraketone, the compound containing sulfur-oxygen bond undergoes polymerization reaction with 2,7-tert-butyl-4,5,9,10-tetraketone, and the obtained polymer containing sulfur-oxygen bond is of formula II: When the tetraketone compound is 1,3,6,8-tetrabromopyrene-4,5,9,10-tetraketone, the compound containing sulfur-oxygen bonds undergoes polymerization reaction with 1,3,6,8-tetrabromopyrene-4,5,9,10-tetraketone, and the obtained polymer containing sulfur-oxygen bonds is of formula III:

6. The method for preparing a polymer containing sulfur-oxygen bonds according to claim 2, characterized in that: The heating step is to react at 120°C for 8-70 hours; the washing step is to wash with acetone and anhydrous ethanol in sequence.

7. An electrode material, characterized in that: The electrode material is prepared from the polymer containing sulfur-oxygen bonds as described in claim 1, and the preparation method comprises: mixing and grinding the polymer containing sulfur-oxygen bonds, a conductive additive and a binder to obtain a slurry; uniformly coating the slurry on the surface of a conductive carbon cloth or conductive carbon paper, and obtaining an electrode material after drying.

8. An electrode material according to claim 7, characterized in that: The mass ratio of the polymer containing sulfur-oxygen bonds, the conductive additive and the binder is 7:2:1; the conductive additive is acetylene black, and the binder is polyvinylidene fluoride.

9. Use of the electrode material as claimed in claim 7 for adsorbing sodium ions in seawater.